Handling owl:sameAs via rewriting - Motik, B; Nenov, Y; Piro, R; Horrocks, I (Association for the Advancement of Artificial Intelligence, 2015)
Rewriting is widely used to optimise owl:sameAs reasoning in materialisation based OWL 2 RL systems. We investigate issues related to both the correctness and efficiency of rewriting, and present an algorithm that guarantees correctness, improves efficiency, and can be effectively parallelised. Our evaluation shows that our approach can reduce reasoning times on practical data sets by orders of magnitude.